The turn of the gradient? Educational differences in breast cancer mortality in 18 European populations during the 2000s. Issue 1 (21st April 2017) - Gadeyne, S.; Menvielle, G.; Kulhanova, I.; Bopp, M.; Deboosere, P.; Eikemo, T.A.; Hoffmann, R.; Kovács, K.; Leinsalu, M.; Martikainen, P.; Regidor, E.; Rychtarikova, J.; et al.
Abstract : This study aims to investigate the association between educational level and breast cancer mortality in Europe in the 2000s. Unlike most other causes of death, breast cancer mortality tends to be positively related to education, with higher educated women showing higher mortality rates. Research has however shown that the association is changing from being positive over non‐existent to negative in some countries. To investigate these patterns, data from national mortality registers and censuses were collected and harmonized for 18 European populations. The study population included all women aged 30‐74. Age‐standardized mortality rates, mortality rate ratios, and slope and relative indexes of inequality were computed by education. The population was stratified according to age (women aged 30‐49 and women aged 50‐74). The relation between educational level and breast cancer mortality was predominantly negative in women aged 30‐49, mortality rates being lower among highly educated women and higher among low educated women, although few outcomes were statistically significant. Among women aged 50‐74, the association was mostly positive and statistically significant in some populations. A comparison with earlier research in the 1990s revealed a changing pattern of breast cancer mortality. Positive educational differences that used to be significant in the 1990s were no longer significant in the 2000s, indicating that inequalities have decreased or disappeared. This evolution is in line with the "fundamental causes" theory which stipulates that whenever medical insights and treatment become available to combat a disease, a negative association with socio‐economic position will arise, independently of the underlying risk factors. Abstract : What's new? Until the 1990s, higher educated women were found to have higher relative risks of dying from breast cancer than lower educated women. But with generalized screening programs and effective treatments becoming available, here the authors wanted to know whether the pattern still held true. Their analysis of data on 18 European populations shows a decrease of the positive association between breast cancer mortality and education in the 2000s. This is in line with the "fundamental causes" theory stipulating that whenever medical insights and treatment become available, a negative association with socio‐economic position will arise, independently of the underlying risk factors.